Video as a Documentation Method: A Qualitative Study of Physiotherapists' Experiences - Silje Bechmann Granås; Ingrid Konstanse Ledel Solem; Ingrid Eitzen; Jenny M. Bergschöld; Cecilie Våpenstad; Wencke Vooren Aase; Trond Halvorsen (Fysioterapeuten)
Aim: To investigate the potential for using video as a method of documentation in physiotherapy for children and adolescents, and potential facilitators and barriers for use and implementation.